Exploring multisectoral collaboration in implementing comprehensive sexuality education framework at the provincial level in Zambia: a qualitative study - Malizgani Paul Chavula; Joseph Mumba Zulu; Isabel Goicolea; Anna-Karin Hurtig (Global Health Action, 2025)
Background In 2014, the Zambian government introduced the Comprehensive Sexuality Education (CSE) framework, decentralising its implementation from the national to the provincial administration. The provincial structures of the Ministries of Health and Education play an important role in providing technical, policy direction and coordination support. However, little research has focused on the role of CSE collaboration at the provincial level. Objectives This study sought to explore multisectoral collaboration dynamics influencing the implementation of the CSE framework at the provincial level in Zambia. Methods This qualitative study involved 29 interviews with diverse stakeholders at the provincial level such as government departments (health, education, etc.), private sector, religious and traditional leaders involved in CSE implementation. We used reflexive thematic analysis, guided by an integrative collaborative governance framework. Results The findings were grouped under collaboration dynamics domains: principled engagement, shared motivation, and capacity for joint action. Barriers to principled engagement included provincial structures and their mandate, exclusion or sidelining of certain actors, inadequate financial transparency, and weak formal relations. Shared motivation included collective understanding of the purpose, a supportive policy environment and consensus in adapting the CSE framework. Capacity for joint action efforts included collaborative training of teachers, joint monitoring, and collaborative to address SRHR challenges. Conclusion This study highlights challenges limiting meaningful engagement, exclusion of some actors, financial constraints, and weak coordination, which hinder collaboration. There is need for enhancing provincial leadership capacity to effectively coordinate stakeholders through enforcement of transparent resource management, collective planning, implementation and monitoring for effective CSE delivery